Analisis Pengaruh TATO, Asset Growth, dan CAR terhadap ROA pada Bank Perekonomian Rakyat Syariah (BPRS) Periode 2021-2024 - annisya putri; Irsad Andriyanto, M.Si. (Jurnal Perbankan Syariah, 2026)
The revocation of business licenses of BPRS by the OJK indicates problems in the financial performance of banks and emphasizes the need to improve profitability as a measure of bank performance. This research is designed to examine the impact of TATO, Asset Growth, and CAR on ROA in BPRS during 2021–2024. This is an associational quantitative study employing secondary data collected from the publication of financial statements of BPRS from 2021-2024 on OJK and related BPRS websites. The analysis of data is performed through panel data regression analysis with Eviews. The findings reveal that TATO has a positive and significant influence on ROA, Asset Growth does not have an impact on ROA, and CAR positively influences ROA. It can be concluded that asset management and capital adequacy play more critical roles than asset growth in improving ROA.